Burden of Influenza and Influenza-associated Pneumonia in the First Year of Life in a Prospective Cohort Study in Managua, Nicaragua. Issue 2 (February 2016) - Gresh, Lionel; Kuan, Guillermina; Sanchez, Nery; Azziz-Baumgartner, Eduardo; Ojeda, Sergio; Melendez, Marlon; Lopez, Roger; Martin, Emily T.; Widdowson, Marc-Alain; Bresee, Joseph; Harris, Eva; Balmaseda, Angel; et al.
Abstract : Background: Influenza is a major public health problem worldwide; however, relatively little is known about influenza in tropical regions, especially for infants. Additional information is required to inform public health policy making, in particular vaccination guidelines. Methods: Between September 2011 and July 2013, we enrolled newborns into the Nicaraguan Birth Cohort Study. Infants were provided primary medical care and actively followed for reverse-transcription polymerase chain reaction–confirmed influenza virus infection when presenting with influenza-like illness or undifferentiated fever. This report presents data pertaining to the first year of life. Results: Of the 518 children enrolled in the study, 441 participated throughout their first year of life, 71 were withdrawn, and 6 died. Overall, 13% of the participants experienced at least 1 laboratory-confirmed influenza virus infection. The overall incidence of influenza was 15.5 cases per 100 person-years [95% confidence interval (CI): 12.2–19.5]. Infants aged 6–11 months experienced significantly higher rates of laboratory-confirmed influenza than infants aged 0–5 months (incidence rate ratio: 2.1; 95% CI: 1.3–3.4). The overall incidence of pneumonia was 52.6 cases per 100 person-years (95% CI: 46.3–59.6). Three percent of the pneumonia cases were influenza associated, and the incidence of influenza-associated pneumonia and hospitalization was 1.7 (95% CI: 0.9–3.5) and 0.22 (95% CI: 0.03–1.55) cases per 100 person-years, respectively. Conclusions: We found a significant burden of influenza and influenza-associated severe respiratory outcomes in infants. Our results support the need to explore the potential value of vaccinating pregnant women and infants aged >6 months, as recommended by the World Health Organization in 2012. Abstract : Supplemental Digital Content is available in the text.